Slummy materialism - Campos Filho, Lindberg (Revista do Instituto de Estudos Brasileiros, 2019)
This is a brief reading exercise of the emblematic novel of Brazilian Naturalism “O cortiço” (1890) of Aluisio Azevedo, taking into account the criticism produced by Antonio Candido in “De cortiço a cortiço” (1974; 1991) at the same time which raises the hypothesis that some of the methods of constructing this narrative may be read, to some extent, the anticipations, sometimes more, sometimes less conscious, of the paradigms of social determination that would guide materialist cultural criticism over the next century.